2012
DOI: 10.1007/s00401-012-0985-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct TDP-43 pathology in ALS patients with ataxin 2 intermediate-length polyQ expansions

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive, adult-onset neurodegenerative disease characterized by degeneration of motor neurons, resulting in paralysis and death. A pathological hallmark of the degenerating motor neurons in most ALS patients is the presence of cytoplasmic inclusions containing the protein TDP-43. The morphology and type of TDP-43 pathological inclusions is variable and can range from large round Lewy body-like inclusions to filamentous skein-like inclusions. The clinical significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Only pTDP-43 skein-like accumulations were observed in tissue from the 5 ALS patient samples examined (Table 3). This is consistent with previous findings suggesting that skein-like inclusions are the predominant pathology in ATXN2 -ALS spinal cord motor neurons (43). From the 4 cases, 11 skein-like accumulations were observed in total (Table 3), with PABP-1 colocalizing with 47% of TDP-43 skein-like inclusions (Figs.…”
Section: Resultssupporting
confidence: 94%
“…Only pTDP-43 skein-like accumulations were observed in tissue from the 5 ALS patient samples examined (Table 3). This is consistent with previous findings suggesting that skein-like inclusions are the predominant pathology in ATXN2 -ALS spinal cord motor neurons (43). From the 4 cases, 11 skein-like accumulations were observed in total (Table 3), with PABP-1 colocalizing with 47% of TDP-43 skein-like inclusions (Figs.…”
Section: Resultssupporting
confidence: 94%
“…Importantly, in vitro experiments showed that the expression products of ATXN2 with intermediate CAG repeats could interact with FUS [75], a DNA/RNA binding protein, which when mutated could cause fALS as a result of impaired RNA intracellular trafficking [75], [76]. In addition, TDP-43 cytoplasmic inclusions in motor neurons of ALS patients harboring intermediate PolyQ repeats primarily showed skein-like or filamentous TDP-43 pathology, whereas ALS cases without ataxin-2 polyQ expansions (n = 13) exhibited abundant large round TDP-43 inclusions [63], [77], and accumulated activated caspase 3 in motor neurons, an upstream event in the TDP-43 disease pathway. The product of ATXN2 with intermediate CAG repeat expansion could increase the presence of TDP-43 in the cytoplasm in a RNA dependent manner [43].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is noteworthy that in addition to the mutations noted above that cause ALS/FTLD-TDP, multiple pathogenic mutations in four other genes (including those encoding ataxin-2, optineurin, NIPA1 and angiogenin) for ALS and/or FTLD-TDP have been discovered that also are linked to TDP-43 pathology thereby suggesting that ALS and FTLD share similar disease mechanisms all of which involve TDP-43 pathology [86, 115, 119, 145]. …”
Section: Tdp-43 Proteinopathies (Ftld-tdp and Als)mentioning
confidence: 99%